PERAN DINAS PEMBERDAYAAN MASYARAKAT DAN DESA (PMD) DALAM PEMBERDAYAAN LEMBAGA ADAT DESA DI KABUPATEN KONAWE KEPULAUAN - Ruslan, Ruslan; Taena, La; Alim, Abdul (Universitas Halu Oleo, 2021)
The purpose of this study is to determine and analyze the role of the PMD Service in Empowering Traditional Institutions in Konawe Kepulauan Regency. The type of data used in this study is descriptive-qualitative research. The technique of determining informants is done by purposive sampling. Data collection techniques are through observation, in-depth interviews and documentation studies. Data analysis techniques are data reduction, data presentation, and verification or conclusion. The results of the study show that the role of the Community and Village Empowerment Service regarding the empowerment of traditional institutions through village funds is still very limited and some of the obstacles experienced, especially during the current pandemic. The formation of customary institutions in Konawe Kegunungan has only formed 5 villages. By seeing the importance of customary institutions, the Community and Village Empowerment Service seeks to develop and facilitate the formation of customary institutions in the Konawe Islands Regency.Keywords: The Role of the Community and Village Empowerment Service, Traditional Institutions